Intraindividual Consistency Between Auditory and Visual Multistability. (February 2020) - Einhäuser, Wolfgang; da Silva, Lucas F. O.; Bendixen, Alexandra
We compared perceptual multistability across modalities, using a visual plaid pattern (composed of two transparently overlaid drifting gratings) and auditory streaming (elicited by a repeating "ABA_" tone sequence). Both stimuli can be perceived as integrated (one plaid pattern, one stream comprising "A" and "B" tones) or segregated (two individual gratings, two tone streams). In the segregated case, either stream or grating can be perceived in the foreground. We queried auditory and visual perception with these three response options. We found that perceptual dominance of the integrated states was correlated across modalities: Participants who were more likely to perceive the plaid were also more likely to perceive the integrated auditory stream. When presenting both stimuli simultaneously and querying the auditory percept, eye-movement data showed that perceiving auditory and visual integration is related on a moment-by-moment basis. This suggests that in part common mechanisms underlie multistability in visual and auditory perception.